Melodies of child: Greek-English phonological interference (Melodias de criança: interferência fonológica grego-inglês) - Babatsouli, Elena (Estudos da Língua(gem), 2019)
In this paper, I will operationalise phonological interference in terms of psycholinguistic and phonological theory by utilizing a Greek-English bilingual girl’s naturalistic speech data for a month at age 2;7, in a language pair that is not researched much in bilingualism. The ultimate goal is to decipher the psycholinguistic and linguistic processes involved in the child’s phonological interference at a qualitative level (the melodic tier), also backed by in-depth quantitative evidence. Phonological interaction is scrutinised in the child’s developing phonologies in an under-represented linguistic context: one of the languages (English) is exogenously acquired and, thus, characterized by compromised exposure in terms of quantity and quality of input. The results sustain the manifestation of phonological interference at both the surface and underlying levels of only certain melodic units in the bilingual’s languages, rather than across the board. The ensuing analyses illuminate the indisputable interaction of several developments at work. Neste artigo, operacionalizarei a interferência fonológica em termos de teoria psicolinguística e fonológica, utilizando dados naturalísticos de uma menina bilíngue greco-inglesa de 2;7 anos, em um par de idiomas que não é muito pesquisado no bilinguismo. O objetivo final é decifrar os processos psicolinguísticos e linguísticos envolvidos na interferência fonológica da criança em um nível qualitativo (o nível melódico), também apoiado por evidências quantitativas. A interação fonológica é examinada nas fonologias em desenvolvimento da criança em um contexto linguístico sub-representado: uma das línguas (inglês) é adquirida exogenamente e, portanto, caracterizada pela exposição comprometida em termos de quantidade e qualidade de entrada. Os resultados sustentam a manifestação da interferência fonológica tanto na superfície quanto nos níveis subjacentes de certas unidades melódicas nos idiomas bilíngues, mas não em todo o quadro melódico. As análises que se seguem iluminam a interação indiscutível de vários desenvolvimentos.